Optimization of cryogenic carbon dioxide removal from CO2-CH4 system by response surface methodology - Babar, M. (Trans Tech Publications Ltd, 2020)
The presence of high CO2content in natural gas reservoirs is one of the significant threats to the environment. Cryogenic CO2capture technology is amongst the emerging technologies used for natural gas purification before customer use. In this research work, the binary CO2-CH4mixture having 75 CO2content is studied. Aspen Hysys simulator with Peng Robinson property package is used for the prediction of phase equilibrium data for the binary mixture. The data obtained through the Aspen Hysys simulator is optimized for the S-V two-phase region for maximum CO2capture. Response surface methodology is used for the optimization of the predicted data. Optimization of the pressure and temperature conditions is done to obtain maximum CH4in the top stream and minimum CO2with minimum energy requirement. In this research work, the pressure and temperature ranges selected from the predicted phase equilibrium data for the optimization are 1 to 20 bar and -65 to -150 °C respectively. At atmospheric pressure and -123.50 °C, the desirability value is maximum, which is 0.843. under these conditions, the CO2and CH4in the top product stream are 1070.72 Kg/hr and 152.04 Kg/hr respectively with an energy requirement of 2.087 GJ/hr. © 2020 Trans Tech Publications Ltd, Switzerland.